The Role of Employers' Associations in Increasing Work Productivity and Conductivity - Purwanto, Agus (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2025)
The rapid development of the industrial world at the global and national levels has given rise to various challenges in terms of industrial relations. Healthy and productive industrial relations depend heavily on the synergy between employers, workers, and the government, all of whom must understand each other and work together to create conditions conducive to industrial sustainability. However, in reality, many countries and industrial sectors face industrial relations problems that can disrupt productivity and work conductivity. This phenomenon does not only occur at the local level, but is also global, where the problems that arise often involve differences in employment policies, social inequality, and economic instability. The design of this study is a Literature Review; Literature review studies are used to collect data or synthesize sources related to research topics from various sources, including journals, books, documentation, the internet and libraries. The literature study method is a series of activities related to the method of collecting library data, reading and recording, and managing writing materials—the method of searching for articles in research journal databases and searching via the internet. The database search used is Google Scholar from 2019 to 2024. For article searches, the keywords used are also included in the data collection, namely " The Role of Employers' Associations in Increasing Work Productivity and Conductivity". Based on the discussion in the journal regarding "The Role of Employers' Associations in Increasing Work Productivity and Conductivity", it can be concluded that employer associations play a very important role in creating a productive and conducive work environment. Through various activities and policies implemented, associations can be a liaison between workers, employers, and the government, and play a role in providing training, counseling, and support to employers to create a more efficient and harmonious workplace.